PENGARUH UMUR PANEN SALAK TERHADAP KADAR VITAMIN C BUAH SALAK MERAH (Salacca edulis Reinw) DARI DESA RIRING KECAMATAN TANIWEL KABUPATEN SERAM BAGIAN BARAT - Elly, Sovian Sesca; Smith, Alwi; Mahulette, Ferymon (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: In Maluku Province, especially in Riring village, there is one variety of salak, namely red salak, which has a nutritional content, namely vitamin C. Vitamin C is a nutrient that acts as an antioxidant. This study aimed to determine the effect of the harvesting age of salak on vitamin C levels in red salak fruit. Methods: This study is an experimental study using a completely randomized design (CRD) with three replications to determine the average vitamin C levels. Analysis of vitamin C levels using the titration method. The data obtained were analyzed using T-test analysis. Results: Based on the study results, the average vitamin C content at harvest age is four months (12.45%), and the average vitamin C content at harvest age is six months (9.53%). The results of the T-test analysis showed that there was a significant effect between the two harvest ages because t-count (19.674)>t-table (2.776). This condition happens because vitamin C is a type of vitamin that is easily oxidized. Conclusion: There is a significant effect between vitamin C levels of red salak fruit aged four months and six months old, where t-count (19.674)> t-table (2.776).